1994
DOI: 10.1093/infdis/169.2.289
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium avium Complex in the Respiratory or Gastrointestinal Tract and the Risk of M. avium Complex Bacteremia in Patients with Human Immunodeficiency Virus Infection

Abstract: Mycobacterium avium complex (MAC) is frequently isolated from the respiratory or gastrointestinal tract of patients with advanced human immunodeficiency virus (HIV) infection. Whether they are at increased risk of MAC bacteremia and whether culture of respiratory tract or stool specimens is useful for predicting bacteremia are unclear. HIV-infected patients with < or = 50 CD4+ cells/microL were prospectively studied. The risk of MAC bacteremia was approximately 60% within 1 year for patients with MAC in either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(68 citation statements)
references
References 13 publications
2
64
0
2
Order By: Relevance
“…Thus, our observations indicate that i.n. exposure to low doses induces protective CD4 + T cells in normal hosts, supporting the knowledge that in severely CD4-deficient persons, such as AIDS patients, a M. avium respiratory infection originating from environmental sources is predictive of mycobacterial dissemination (Chin et al, 1994 ;Inderlied et al, 1993).…”
Section: Discussionsupporting
confidence: 67%
“…Thus, our observations indicate that i.n. exposure to low doses induces protective CD4 + T cells in normal hosts, supporting the knowledge that in severely CD4-deficient persons, such as AIDS patients, a M. avium respiratory infection originating from environmental sources is predictive of mycobacterial dissemination (Chin et al, 1994 ;Inderlied et al, 1993).…”
Section: Discussionsupporting
confidence: 67%
“…This ability has been frequently described as an important prerequisite for an opportunistic pathogen. Two recent prospective studies have demonstrated that HIV-positive patients with colonization of respiratory or gastrointestinal tract by MAC had a greater risk of MAC dissemination than those without colonization (Havlik et al 1993;Chin et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Genomic restriction fragment patterns of Maa from hospital water isolates are similar to those from AIDS patient isolates [5]. Numerous studies have attempted to determine the routes, oral or aerosol, leading to Maa infection in AIDS patients but no evidence was related to one and a combination of both routes is likely [22,83,144].…”
Section: Transmission and Route Of Infectionmentioning
confidence: 99%